Incidence and progression of diabetic retinopathy and blindness in Indonesian adults with type 2 diabetes - Muhammad Bayu Sasongko; Gandhi Anandika Febryanto; Supanji Haryanto; Firman Setya Wardhana; Yeni Dwi Lestari; Anggraeni Puspita; Felicia Widyaputri (PLoS ONE, 2025)
Objectives To report the incidence and progression rate of diabetic retinopathy (DR) and blindness in Indonesian adults with type 2 diabetes. Methods This was a prospective cohort study of 899 adults aged >30 years with confirmed type 2 diabetes. All participants underwent standardized clinical and eye examinations. Two-field retinal photographs were taken. DR was graded by trained grader masked to participants’ clinical details. We categorized DR as follows: mild, moderate, severe non-proliferative (NPDR), and proliferative DR (PDR). Additional category of vision-threatening DR (VTDR) included severe NPDR or more, or moderate NPDR with clinically significant macular edema. Blindness was defined as visual acuity ≤3/60. At least 1-step progression was categorized as DR progressing. Cox-proportional hazard model was used. Results The incidence and progression of DR were 34.6 and 35.1, and incidence of VTDR and blindness were 24.5 and 8.33/1000 person-years, respectively. Longer diabetes duration was associated with increasing the risk of developing DR (Hazard ratio 1.37 [95% confidence interval 1.10–1.72]) and VTDR (2.00 [1.60–2.50]) and progressing DR (1.50 [1.23–1.84]) in 5 years. Obesity was associated with increased risk of developing DR (1.75 [1.14–2.68]) and the presence of gangrene (2.54 [1.49–4.35]) and neuropathy (1.50 [1.07–2.10]) at baseline increased the risk of progressing DR in 5 years. Living in rural area was associated with increased risk of blindness (2.50 [1.03–5.88]). Conclusions We reported the incidence and progression rate of DR, VTDR, and blindness, and documented that longer diabetes duration increased the risk of DR and VTDR in 5 years.